Polycrystalline silicon thin films on glass deposited from chlorosilanes at intermediate temperatures - Benvenuto, Ariel Gastón (2012)
We show that commercial float glass can be used as a substrate to deposit polycrystalline silicon (poly-Si) by chemical vapor deposition from trichlorosilane at temperatures between 740 and 870 ºC. By using scanning electron microscopy an average grain size lower than 0.4 μm was observed, with a columnar structure suitable for the electrical conduction in photovoltaic cells. X-ray diffraction reveals a strong (2 2 0) preferential orientation of the films, which is indicative of a low density of intra-grain defects. Atomic force microscope images reveal a conical structure, with a root mean square roughness of 65 nm for samples of around 3 μm in thickness. This natural texture is a positive characteristic from the point of view of light trapping. By using boron tribromide as a doping agent, degrees of doping ranging from intrinsic to clearly p-doped were obtained, as shown by dark conductivity measurements as a function of temperature. The process, the reactants and the substrate used are of low cost and proved to be adequate for direct poly-Si deposition.